An examination of corporate reporting, environmental management practices and firm performance - Montabon, Frank; Sroufe, Robert; Narasimhan, Ram (Journal of Operations Management, 2007)
AbstractDespite the growing interest in environmental management practices (EMPs), research to date has typically analyzed a limited range of these practices and used traditional data sources. In contrast, this paper uses an innovative data source to explore EMPs. We use a more comprehensive set of the practices than prior works in order to test relationships between EMPs and firm performance. The data used in this study comprised environmental and business performance data from 45 corporate reports. Content analysis is used to gather the data and canonical correlation is used for analysis in a two‐step process in order to explore the relationships between EMPs and performance measures. Results support previously posited relationships based on traditional data and indicate that EMPs are associated with firm performance.